Multiple myeloma: Evidence based management. - Saleh, Abu Jafor Md (Bangladesh Journal of Medicine, 2024)
Multiple myeloma is a neoplasm of plasma cell which comprises 10% of all hematological malignancies. First case myeloma described in 18441 but medical treatment was commenced from 1960 with melphalan and prednisolone. In 1999 thalidomide was discovered and after three years huge change occurred with development of Bortezomib and Lenalidomide. Most common symptom is pain and progressively complicates with anemia, renal impairment, hypercalcemia which are better known as CRAB.Current treatment is triplet combination with VTD, VCD or RVD as standard of care2. The golden drug “melphalan” which was discovered in 1958, now used in conditioning purpose for autologous stem cell transplant. Another milestone is the discovery of anti-CD38 monoclonal antibody called Daratumumab which is approved in November 2015 to use as 4th agent with any of the above triplets or as single agent for selected patients.After relapse of 3rd or 4th line treatment including autologous stem cell transplant, where apparently no hope for further therapeutic option, chimeric antigen receptor T cell (CAR-T) therapy showed excellent remission rate above 60% and got US FDA approval in March 20212. In Bangladesh we are practicing with 3 or 4 drug induction followed by autologous stem cell transplantation, and then oral maintenance. Almost 150 autologous stem cell transplant has been done in Dhaka and Chattogram. Hope in future we will be able to start CAR-T therapy in our country. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 148